Individual Experience dan Persepsi Pedagang: Relasi Pengalaman Individual Dan Persepsi Pedagang Terhadap Bank Syariah - Fajar Hajaru; H Hardivizon (Institut Agama Islam Negeri (IAIN) Curup, 2016)
The main differences of shariah institution and conventional can be indentified in the two system–application of loss and profit sharing; interest. Loss and profit sharing as an alternative system, or mechanisme to alter the ribawi system. In this context, the research applies a grounded theory. The result shows that their perception toward profit and loss sharing in islamic bank, essentially is based on individual experience. It is also a foundation for their choice toward islamic bank. Data informs that consumers interest to choose islamic bank because of profit and loss sharing. Keywords : Individual experience, perception, consumers, islamic bank, profit and loss sharing.